Infection control in the UK: an antimicrobial resistance perspective - Henry, Elecia Jaime; Smith, Robert; Collins, Michael; Bird, Susan; Gowland, Pauline; Cassella, John Paul (International Journal of Infection Control, 2017)
The spread of healthcare-associated infections has become a matter of global concern. These infections, which were once isolated to hospital settings, have emerged in the community. Reduced infection control practices are a major cause of this rapid spread of infections, which has led to the increase in the occurrence of multi-drug resistant organisms. The state of infection control in the United Kingdom is of extreme importance because of several reported cases of infections caused by these organisms. In addition to antimicrobial usage in human medicine, antimicrobial agents used in agriculture must be considered as major factors in the prevalence of resistant organisms and the implications to the UK. However, this increased occurrence of antimicrobial resistant bacteria and their resulting infections could be reduced with the application of effective policies for antibiotic use in agricultural environments, stringent decontamination and sterilisation techniques and better regulations that encourage the search for, and development of, new and novel drugs.